IMPROVING COGNITIVE SOCIAL-SKILLS BY BEHAVIOR MODIFICATION TECHNIQUES: A STUDY ON ISLAMIC PRIMARY SCHOOL STUDENTS IN INDONESIA - Diana Mutiah (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2023)
Student behaviour, in general, is still a problem. Many students still need to be responsible for school assignments and do not do homework or other assignments. Concern for the environment is still very low. Like they were throwing trash in its place. Therefore, the ability of the teacher to intervene in modifying student behaviour is essential. This research was carried out to provide Behavior Modification Models for improving children's social skills. It was divided into four parts: (1) a preliminary study, (2) a workshop on behaviour modification, (3) a field test on the behaviour modification models and (4) improvement to the models following the test results. The participants consisted of 225 Islamic elementary school students in Indonesia. The data were examined by SEM (Structural Equation Modeling). The students' skills were developed using behaviour modification techniques, namely modelling, reinforcement, token economy, punishment, prompt, relaxation and shaping. The result suggested the importance of cognitive process (awareness) and learning contracts through class discussion for improving children's social skills. An interesting finding is that there is a significant increase in the application of behaviour modification techniques when students are involved in thinking and being involved in determining activities or actions that disturb the class and the consequences that will be given if students commit several violations in class through contract learning or agreement techniques, modelling, reinforcement, token economy, punishment, time out, relaxation and awareness of cognition.